(3GdRNjQI aj GdWHs - (3KGHJ Hf bQI Hf RgQhf GdMQGfj GdUCHrj, CHh GdMSf,J (B288 (3g` s
(3ChdgG (B:s
(3Chd GdehLhO efg GdHGH GdChd ai LhGeY cdGe jSJYGf aCeG GdLeGY ajLH EdG GdTHb GdTOjO GdTghI GdZRjQ Gdefi s
(3BNQgG (B:s
(3BNQ GdehLhO efg (B: (3CeG GdCWYeI GdeDdaI GdRGFOI ai GdHGg aGdgGjS Ydi gPg GdUaI jDNP dMe QNU hjWHN MJi jJgQi Ke jfRY YXGeg Sei GdHbQ s
(3HgG fXGe GdJYbjHIs
(3Chd GdhQbGJ GdChdi fGbUIs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B2 - (3U (B98 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B3 - (3U (B101s
(3JHUQGJ GdCUd (B:s
(3GdfSNI fGbUI GdChd , eHJhQI GdBNQ , HgG NQe s
Keywords: (3GdWHs